2004
DOI: 10.1002/jbt.20015
|View full text |Cite
|
Sign up to set email alerts
|

Global changes in the expression patterns of RNA isolated from the hippocampus and cortex of VX exposed mice

Abstract: One of the established activities of the nerve agent VX is inhibition of the enzyme acetylcholinesterase (AChE). This inhibition affects the cholinergic nervous system by decreasing the activity of the neurotransmitter-hydrolyzing enzyme cholinesterase (ChE). In an effort to gain a more comprehensive understanding of the molecular pathways affected by low-level exposure to VX, an expression profiling approach was used to identify genes with altered RNA expression patterns after exposure.Specifically, mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Oligonucleotide microarrays are commonly used to simultaneously measure the mRNA levels of thousands of genes in a cell and are capable of detecting even subtle changes in gene expression. Gene expression profiling has been successfully used to investigate the mechanisms of toxicity and resulting effects of various CWAs [19-24]. …”
Section: Introductionmentioning
confidence: 99%
“…Oligonucleotide microarrays are commonly used to simultaneously measure the mRNA levels of thousands of genes in a cell and are capable of detecting even subtle changes in gene expression. Gene expression profiling has been successfully used to investigate the mechanisms of toxicity and resulting effects of various CWAs [19-24]. …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, changes in gene expression levels have been reported using regional dissections of the rodent hippocampus. For example, microarray analysis has been used in the hippocampus for a variety of downstream genetic analyses in animal models, including studies of alcohol consumption (Saito et al,2002), aging (Blalock et al,2003), amyloid overexpression (Dickey et al,2003; Reddy et al,2004), antidepressant administration (Drigues et al,2003), epilepsy (Becker et al,2003; Newton et al,2003), hippocampal cytoarchitecture (Zhao et al,2001; Lein et al,2004), hypergravity (Del Signore et al,2004), hypoxia/ischemia (Gilbert et al,2003; Qiu et al,2004), learning and memory (Cavallaro et al,2001,2002), nerve agent exposure (Blanton et al,2004), and traumatic brain injury (Marciano et al,2002), among others. Regional analyses of hippocampal gene expression has also been performed on postmortem human brain tissues, including studies assessing AD (Loring et al,2001; Colangelo et al,2002; Blalock et al,2004; Lukiw,2004) and epilepsy (Becker et al,2002,2003; Lukasiuk and Pitkänen,2004).…”
mentioning
confidence: 99%
“…C57BL/6 mice were exposed to low doses (0.2 or 0.4 LD 50 ) of VX five times per week (Monday to Friday) for 2 weeks. Expression of BDNF in mouse brain was measured at 2 or 72 h after the last VX exposure, similar to time points measured by Blanton et al (2004) using microarrays, in which they observed a transient increase in gene clusters following repeated exposure to sublethal doses of VX. In our study, we hypothesized that BDNF levels would be affected by 2 h post-exposure and return to baseline by 72 h post-exposure.…”
mentioning
confidence: 64%
“…there has been minimal research into the molecular mechanisms of exposure to sublethal doses of CWNA, with the exception of Blanton et al (2004), who evaluated the effects of repeated exposure to sublethal doses of VX on neuronal gene expression using microarrays.…”
mentioning
confidence: 99%